Seed priming improves early seedling vigor, growth and productivity of spring maize - Hafeez ur Rehman; Hassan Iqbal; Shahzad M A Basra; Irfan Afzal; Muhammad Farooq; Abdul Wakeel; Ning WANG (Journal of Integrative Agriculture, 2015)
Potential of seed priming treatments in improving the performance of early planted maize was evaluated against timely planting. Seeds of maize hybrid FH-810 were soaked in water (hydropriming), CaCl2 (2.2%, osmopriming), moringa leaf extracts (MLE 3.3%, osmopriming) and salicylic acid (SA, 50 mg L−1, hormonal priming) each for 18 h. Untreated and hydroprimed seeds were taken as control. Seeds primed with SA took less time in emergence and had high vigor in early planted maize. Amongst treatments, hormonal priming, reduced the electrical conductivity, increased the leaf relative and chlorophyll contents followed by osmopriming with CaCl2 at seedling stage. Likewise, plant height, grain rows and 1 000-grain weight, grain and biological yield and harvest index were also improved by seed priming; however hormonal priming and osmopriming with MLE were more effective in this regard. Improved yield performance by hormonal priming or osmopriming with MLE in early planting primarily owed to increased leaf area index, crop growth and net assimilation rates, and maintenance of green leaf area at maturity. In conclusion, osmopriming with MLE and hormonal priming with SA were the most economical treatments in improving productivity of early planted spring maize through stimulation of early seedling growth at low temperature.